2012
DOI: 10.1038/nchembio.939
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic oligonucleotides recruit ILF2/3 to RNA transcripts to modulate splicing

Abstract: We describe a new technology for recruiting specific proteins to RNA through selective recognition of heteroduplexes formed with chemically modified antisense oligonucleotides (ASOs). Typically, ASOs function by hybridizing to their RNA targets and blocking the binding of single-stranded RNA–binding proteins. Unexpectedly, we found that ASOs with 2′-deoxy-2′-fluoro (2′-F) nucleotides, but not with other 2′ chemical modifications, have an additional property: they form heteroduplexes with RNA that are specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
100
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 47 publications
1
100
0
1
Order By: Relevance
“…Hybridization of ISIS 396443 to ISS-N1 prevents the recruitment of the splicing repressor heterogeneous nuclear ribonucleoprotein A1 and A2, and results in almost complete SMN2 exon 7 inclusion in cell culture (Hua et al, 2008;Rigo et al, 2012). Robust splicing correction and SMN protein production are also observed in the central nervous system (CNS) of mice transgenic for SMN2 after central administration of ISIS 396443 (Hua et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybridization of ISIS 396443 to ISS-N1 prevents the recruitment of the splicing repressor heterogeneous nuclear ribonucleoprotein A1 and A2, and results in almost complete SMN2 exon 7 inclusion in cell culture (Hua et al, 2008;Rigo et al, 2012). Robust splicing correction and SMN protein production are also observed in the central nervous system (CNS) of mice transgenic for SMN2 after central administration of ISIS 396443 (Hua et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Intracerebroventricular infusions and i.p. bolus injections (Rigo et al, 2012) were performed as previously described. For i.c.v.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Indeed, a recent study has demonstrated that F-RNA antisense oligonucleotides can direct the recruitment of protein complex ILF2/3 to induce exon skipping, while corresponding 2'-O-(2-methoxyethyl) oligonucleotides are unable to do that. [20] Overall, introduction of fluorine substituent(s) constitutes an effective approach to improve the therapeutic potential of nucleic acid analogues.…”
Section: Introductionmentioning
confidence: 99%
“…FRNA-modified oligonucleotides (ONs) have found widespread use as nucleic acid aptamers, 1 ribozymes, 2 antisense agents, 3 allele-selective gene silencing, 4 splice-switching, 5 single-stranded siRNA, 6 and anti-microRNA 7 oligomers. FRNA-modified siRNAs possess unique gene silencing properties 8,9 and are currently being evaluated in human trials for the treatment of genetic disorders.…”
mentioning
confidence: 99%